THE ROLE OF HYGIENE EDUCATION IN MAINTAINING THE HEALTH OF CHILDREN AND ADOLESCENTS (International Congress on Economics, Management and Business Studies, 2026)
Maintaining and improving the health of children and adolescents is a priority for modern society. During childhood and adolescence, fundamental habits are formed, including hygiene habits, which later determine a person's quality of life. Adherence to personal and public hygiene rules helps prevent infectious diseases, promote healthy physical development, and improve performance.